2008
DOI: 10.1177/0146167208319692
|View full text |Cite
|
Sign up to set email alerts
|

The Thin Line Between Reality and Imagination: Attachment Orientations and the Effects of Relationship Threats on Sexual Fantasies

Abstract: The authors examined the effects of relationship threats on sexual fantasies. In two studies, participants described a sexual fantasy following an imagination task and reported their attachment orientations. In Study 1, participants imagined relationship or nonrelationship threat scenes. Results indicated that relationship threat led to fantasies that involved interpersonal distance and hostility themes. Furthermore, following relational threat, women and more anxiously attached individuals were most likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…In an initial series of studies, participants imagined relationship-threatening scenes (e.g., a partner's infidelity) or non-relationship threatening scenes (failure on an exam) and then rated or described their desire to have sex, reasons for engaging in sex, and what sexual activities they would like to engage in, that is, their sexual fantasies (Birnbaum, Svitelman, Bar-Shalom, & Porat, 2008;Birnbaum, Weisberg, & Simpson, 2010). Results indicated that relationship threat strengthened both self-enhancement motives and pro-relationship motives, suggesting that people use sex both to maintain their self-esteem and to repair the threatened relationship.…”
Section: Attachment Sex and Distress Regulationmentioning
confidence: 99%
“…In an initial series of studies, participants imagined relationship-threatening scenes (e.g., a partner's infidelity) or non-relationship threatening scenes (failure on an exam) and then rated or described their desire to have sex, reasons for engaging in sex, and what sexual activities they would like to engage in, that is, their sexual fantasies (Birnbaum, Svitelman, Bar-Shalom, & Porat, 2008;Birnbaum, Weisberg, & Simpson, 2010). Results indicated that relationship threat strengthened both self-enhancement motives and pro-relationship motives, suggesting that people use sex both to maintain their self-esteem and to repair the threatened relationship.…”
Section: Attachment Sex and Distress Regulationmentioning
confidence: 99%
“…This pattern may be particularly marked in the sexual realm, because of highly avoidant individuals' tendency to use sex to maximize distance, even in the most intimate interactions (e.g., Birnbaum, 2010;. To be sure, a recent study has shown that relationship threat induced a negative view of others in highly avoidant individuals' sexual fantasies (Birnbaum et al, 2008). This negative view of others may eventually lead to sexual disengagement, at least from one's partner, as our findings suggest.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to complete a packet of questionnaires at their own pace (all questionnaires were in Hebrew). Following the instructions, participants began the relationship visualization task, which was adapted from a procedure developed by Birnbaum et al (2008). Specifically, they were randomly assigned to one of three visualization conditions: (a) a relationship threat scene in which they were asked to imagine that their romantic partner was considering breaking up with them; (b) a non-relationship threat scene in which participants were asked to imagine that they had just failed in an important exam (this condition was included to test whether sexual motivation is affected by global aversive feelings versus specific threats to the relationship); and (c) a non-threatening scene in which participants were asked to imagine that their partner was going to the grocery store.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations